Methanogens and Hydrogen Sulfide Producing Bacteria Guide Distinct Gut Microbe Profiles and Irritable Bowel Syndrome Subtypes. (6th December 2022) - Villanueva-Millan, Maria J.; Leite, Gabriela; Wang, Jiajing; Morales, Walter; Parodi, Gonzalo; Pimentel, Maya L.; Barlow, Gillian M.; Mathur, Ruchi; Rezaie, Ali; Sanchez, Maritza; Ayyad, Sarah; Cohrs, Daniel; et al.
Abstract : INTRODUCTION: Irritable bowel syndrome (IBS) includes diarrhea-predominant (IBS-D) and constipation-predominant (IBS-C) subtypes. We combined breath testing and stool microbiome sequencing to identify potential microbial drivers of IBS subtypes. METHODS: IBS-C and IBS-D subjects from 2 randomized controlled trials (NCT03763175 and NCT04557215) were included. Baseline breath carbon dioxide, hydrogen (H2 ), methane (CH4 ), and hydrogen sulfide (H2 S) levels were measured by gas chromatography, and baseline stool microbiome composition was analyzed by 16S rRNA sequencing. Microbial metabolic pathways were analyzed using Kyoto Encyclopedia of Genes and Genomes collection databases. RESULTS: IBS-C subjects had higher breath CH4 that correlated with higher gut microbial diversity and higher relative abundance (RA) of stool methanogens, predominantly Methanobrevibacter, as well as higher absolute abundance of Methanobrevibacter smithii in stool. IBS-D subjects had higher breath H2 that correlated with lower microbial diversity and higher breath H2 S that correlated with higher RA of H2 S-producing bacteria, including Fusobacterium and Desulfovibrio spp. The predominant H2 producers were different in these distinct microtypes, with higher RA of Ruminococcaceae and Christensenellaceae in IBS-C/CH4 + (which correlated with Methanobacteriaceae RA) and higher Enterobacteriaceae RA in IBS-D. Finally, microbial metabolic pathway analysis revealed enrichment of Kyoto Encyclopedia of Genes and Genomes modules associated with methanogenesis and biosynthesis of methanogenesis cofactor F420 in IBS-C/CH4 + subjects, whereas modules associated with H2 S production, including sulfate reduction pathways, were enriched in IBS-D. DISCUSSION: Our findings identify distinct gut microtypes linked to breath gas patterns in IBS-C and IBS-D subjects, driven by methanogens such as M. smithii and H2 S producers such as Fusobacterium and Desulfovibrio spp, respectively.